NILAI ACUAN PADA KAYU AREN BERDASARKAN PENGUKURAN SIFAT MEKANIK KAYU - La Welendo; Try Sugiyarto Soeparyanto (STABILITA || Jurnal Ilmiah Teknik Sipil, 2013)
AbstractWood is a natural product that has a variety of properties and strength. Wood or palm sugar (Arenga pinnata) is a tree that produces industrial materials have long been familiar. Information on physical and mechanical properties of wood are very useful and powerful class of timber and determine alternate picking the most effective use of wood and profitable.In this research material which is utilized is timbered sugar palm which consisting of two variables which is sugar palm wood variables that getting production and sugar palm wood that doesn't get production again that each variable consisting of five samples. The research was conducted in two different places, namely in the Materials Engineering Laboratory Department of Civil Engineering and Construction UHO to measure the physical properties of wood that is the original moisture content and density of the wood and in the department of materials engineering laboratory UHO to measure the mechanical properties of wood that is test the compressive strength and tensile the sugar palm.Base physical character measurement, sugar palm wood that temporary gets average value production titrate water as big as 2,477 % and timbered specific gravity average values as big as 0,695 and timbered sugar palm that don't get productions with average value titrates water as big as 2,677 % and and timbered specific gravity average values as big as 0,689 so timbered sugar palms of timbered physical characters come under class wood II by appreciative strong classes be “light weight”. Meanwhile bases mechanical character measurement, sugar palm wood that temporary gets pressing strong average value production as big as 2606,07 kg/cm2 and strength average value pulls as big as 1411,85 kg/cm2 and sugar palm wood that doesn't get production with pressing strong average value as big as 1317,89 kg/cm2 and and strength average value pulls as big as 852,24 kg/cm 2  so sugar palm wood of timbered mechanical character categorised timbered I class.Keywords: palm wood, wood physical properties, mechanical properties of wood, wood strength class AbstrakKayu adalah produk alam yang mempunyai sifat dan kekuatan yang beragam. Kayu aren atau enau (Arenga pinnata) merupakan pohon yang menghasilkan bahan-bahan industri sudah sejak lama di kenal. Informasi mengenai sifat fisis dan mekanik kayu sangat bermanfaat dan menentukan kelas kuat kayu serta memilih alternatif penggunaan kayu yang paling efektif dan menguntungkan.Dalam penelitian ini bahan yang digunakan adalah kayu aren yang terdiri dari dua variabel yaitu variabel kayu aren yang sedang berproduksi dan kayu aren yang tidak berproduksi lagi masing-masing terdiri dari lima sampel. Penelitian ini dilakukan di dua tempat berbeda yaitu di Laboratorium Teknik Bahan dan Kontruksi Jurusan Teknik Sipil UHO untuk mengukur sifat fisik kayu yaitu kadar air asli dan berat jenis kayu serta di laboratorium bahan jurusan teknik mesin UHO untuk mengukur sifat mekanik kayu yaitu menguji kekuatan tekan dan tarik pada kayu aren.Berdasarkan pengukuran sifat fisik, kayu aren yang sementara berproduksi nilai rata-rata kadar air sebesar 2,477%  dan nilai rata-rata berat jenis kayu sebesar 0,695 serta kayu aren yang tidak berproduksi dengan nilai rata-rata kadar air sebesar 2,677 % dan dan nilai rata-rata berat jenis kayu sebesar 0,689 sehingga kayu aren dari sifat fisik kayu tergolong kayu kelas II dengan nilai kelas kuat adalah “berat ringan”. Sedangkan berdasarkan pengukuran sifat mekanik, kayu aren yang sementara berproduksi nilai rata-rata kuat tekan sebesar 2606,07 kg/cm2 dan nilai rata-rata kuat tarik sebesar 1411,85 kg/cm2 serta kayu aren yang tidak berproduksi dengan nilai rata-rata kuat tekan sebesar 1317,89 kg/cm2 dan dan nilai rata-rata kuat tarik sebesar 852,24 kg/cm2 sehingga kayu aren dari sifat mekanik kayu tergolong kayu kelas I.Kata kunci: kayu aren, sifat fisik kayu, sifat mekanik kayu, kelas kuat kayu